2022
DOI: 10.1111/ina.13071
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assessment of organophosphate flame retardants, plasticizers, trace metals, and house dust mite allergens in settled house dust

Abstract: Settled house dust (SHD) is a reservoir for various contaminants, including endocrine‐disrupting chemicals (EDCs), trace metals, and house dust mite allergens. This study aimed to characterize various chemical and biological contaminants in SHD and identify determinants governing the indoor contaminants. In total, 106 SHD samples were collected from 106 houses in Seoul and Gyeonggi Province, Korea, in 2021. Bedding dust samples were collected from 30 of these 106 houses. All participants completed a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…As shown in Figure S6 , most OPFRs were mainly apportioned to this source in PMF, especially for TCEP, TCPP, EHDPP, and TnBP. TCPP and TPHP are mainly applied in polyurethane foam; 39 , 40 EHDPP is primarily used in food packaging, paints, and rubber, 8 , 40 while TMPP and TBOEP are used in abandoned automobiles and electric wires. 41 Like our results, Wang et al 42 also found waste recycling as an important source of environmental chlorinated- and aryl-OPFRs by measuring dust and soil samples collected from a waste recycling area.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Figure S6 , most OPFRs were mainly apportioned to this source in PMF, especially for TCEP, TCPP, EHDPP, and TnBP. TCPP and TPHP are mainly applied in polyurethane foam; 39 , 40 EHDPP is primarily used in food packaging, paints, and rubber, 8 , 40 while TMPP and TBOEP are used in abandoned automobiles and electric wires. 41 Like our results, Wang et al 42 also found waste recycling as an important source of environmental chlorinated- and aryl-OPFRs by measuring dust and soil samples collected from a waste recycling area.…”
Section: Results and Discussionmentioning
confidence: 99%